Actuarial and financial risks in life insurance, pensions and household finance - Luca Regis (MDPI, 2018)
The recent regulatory changes, together with the increasing awareness of the variety of sources of uncertainty that affect the activities of insurance and pension funds, have generated increasing attention towards insurance risk management theory and practice. Against this background, this Special Issue collects relevant contributions on a variety of issues encompassing longevity risk modelling, solvency requirements, risk management, and risk sharing. This collection of papers provides insights, from both a theoretical and a practical perspective, into the modeling and management of actuarial and financial risks for institutions and households.
Keywords: 330